Factors Influencing Sharia Property Purchase Decisions: Tasnim Property Case Study - Setiawan, Budi Susilo; Asnawi, Yudha Heryawan; Hartono, Sri (International Journal of Artificial Intelligence Research, 2024)
Study This aiming For analyze influence product, price,location, promotion, word of mouth, style life, technology and information to interest buy and decision purchase Sharia property at Tasnim Property, as well as role interest buy as intervening variable. Research done use approach quantitative with voluntary sampling technique. A total of 195 respondents who had do survey to Tasnim Property office fills online questionnaire. Data was analyzed using SEM-PLS version 4. Research results show that variable product, price, promotion,word of mouth, style life and technology influential significant to interest buy. However, the location and information No influential significant. Product, price,promotion, and word of mouth also have an influence. significant to decision purchase, while location, style life,technology and information no. Interest in buying own influence significant to decision purchase. In No direct,variable product, price, promotion, word of mouth, style life,and technology also influences decision purchase through interest buy. Implications managerial from study This that is the need for segmentation, targeting, and positioning (STP) strategies and optimization influential variables significant to decision purchase, namely products, prices, promotions, and word of mouth